Prevalence of co-morbidities in hospitalized patients with COVID-19 in a COVID dedicated hospital - Kinge, Kirti Vinayak; Chavan, Smita Santosh; Adsul, Balkrishna; Kumbhar, Maharudra (International Journal Of Community Medicine And Public Health, 2021)
Background: A novel corona virus causing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection become a public health emergency of international concern. The infection has increased and caused pandemic. Underlying co-morbidities may worsen the clinical outcome. So, more attention is to be given to COVID patients with co-morbidities. Few studies have been conducted on the prevalence of predominant chronic diseases with COVID-19. Taking into consideration the above factors, a study has been undertaken to assess the prevalence of co-morbidities in a COVID dedicated hospital. Methods: A centre based retrospective study was carried out at a COVID dedicated hospital, Mumbai. All admitted patients of COVID 19 in a COVID dedicated hospital, Mumbai were selected in 4 and half months (19th March 2020 to 31st July 2020) by universal sampling technique. Patients above 20 years were included in the study and patients below 20 years were excluded from the study. Ethics Committee approval taken from an institutional ethics committee. Results: All 6072 patients who were above 20 years were included in the study. Mean age was 48 years and 67.7% were male. The prevalence of various co-morbidities was 25% for hypertension, 22.3% for diabetes mellitus, 5.2% for chronic kidney disease, 1.7% for chronic obstructive pulmonary disease, 0.9% for cerebrovascular disease and 0.3% for one or the other malignancy. Conclusions: It has been concluded that various co-morbidities are present in patients with COVID-19 which may worsen the clinical outcome. So, more attention is to be given to COVID patients with co-morbidities.